Bridging and chelation in organoantimony(V) chemistry - Gibbons, Martin Neil (1996)
The work presented in this thesis is primarily concerned with the structural aspects of bridging and chelation in organoantimony(V) chemistry. The thesis may be essentially divided into two main parts. The first part examines the reactions of a number of halogenated oxo-bridged organoantimony compounds (themselves subject to a study in Chapter 2) with a range of potentially bidentate groups (arsinates, phosphinates and carboxylates) to assess the capability of these groups to bridge between antimony centres. Spectroscopic and crystallographic results illustrate that arsinate groups were successfully employed in the formation of quadruply bridged compounds, whereas both arsinate and phosphinate groups enabled the preparation of several triply bridged compounds. In contrast, the shorter 'bite-length' carboxylate groups were unable to span across antimony centres in an analogous manner, although reactions between [Ph2SbBrO]2 and acetate or trimethylacetate groups led to formation of the carboxylate bridged tetra-antimony compounds, [Ph8Sbil4(mu-O)4(mu-O1.2)2(mu-O2CR3 )2]. The second part is concerned with antimony(V) stereochemistry. Incorporation of the chelating 2,2' -biphenylylene group led to manipulation of the coordination geometry at antimony and the preparation of compounds of the type, PhSb(2,2' -C12H8)X2,with square pyramidal monomeric units. The compounds, however, possess weak intermolecular connections, giving rise to dimers in the solid state and an increase in the coordination number at antimony. In addition, the related compound, PhSb (o-02C6Cl4)Cl2, also showed distinct Lewis acidity at antimony and was isolated as a diethyl ether adduct. An additional area of work is also briefly investigated in Chapter 6. This work examines reactions between halogenated phenylantimony compounds and transition metal anions, to yield complexes incorporating the Ph2Sb or PhSb moieties.